BUILDING STOCK PORTFOLIO USING PETER LYNCHâS INVESTMENT STRATEGY IN INDONESIA STOCK EXCHANGE - Owen, Jeremy
Peter Lynch’s investment strategy is one of the most superior strategy back in the 1970s until the 1990s. His Magellan Fund managed to double the return of S&P500 index for 13 years in a row. He shared his strategy in his book “One Up on Wall Street” where he explained how to build the winning portfolio. Based on this book this research was built. It will help retail investors to beat the market and gain a significant amount of growth consistently. Lynch’s strategy will be the main tool for portfolio construction in this research. The focus of this research is to build and measure the portfolio in Indonesian stock market., where this research has to screen roughly 600 stocks. The timespan for this research is two years depending on the market condition such as bearish market of 2015-2017, bullish market of 2016-2018 and lastly, sideways market 2017-2019. In total, this research will have 6 portfolios, divided into 2 methods, based on equally weighted and market capitalization. The methods will be divided again into 3 portfolios based on market condition stated earlier. The result will also be measured using Sharpe ratio, Treynor ratio and Jensen’s Alpha ratio compared with the market performance. The result showed that only two portfolios manage to beat the market performance which are the equally weighted method during bearish market and market capitalization method during sideways market. The others underperformed compared to the market.